2008
DOI: 10.1038/jp.2008.102
|View full text |Cite
|
Sign up to set email alerts
|

Families' views upon experiencing change in the neonatal intensive care unit environment: from the ‘baby barn’ to the private room

Abstract: Background: Parents whose newborns were cared for in the old neonatal intensive care unit (NICU) environment and then moved to the new NICU environment describe their impressions of the impact upon their infant's care, information access and support, of the two care settings.Objectives: To determine the perceptions of parents in the NICU regarding noise, light, space, access to caregivers and personal privacy as they experience both old and new NICU environments in the continuum of care for their infant.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 7 publications
(4 reference statements)
3
74
1
Order By: Relevance
“…This finding was surprising, as increased privacy has been cited in several studies 21,26,27 as a primary benefit of SFR NICUs. Mothers pointed out that although they were in a private room they could not control who entered and so the potential that they could be interrupted while pumping made the mothers uncomfortable.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This finding was surprising, as increased privacy has been cited in several studies 21,26,27 as a primary benefit of SFR NICUs. Mothers pointed out that although they were in a private room they could not control who entered and so the potential that they could be interrupted while pumping made the mothers uncomfortable.…”
Section: Discussionmentioning
confidence: 59%
“…Staff perceived that parents were afforded greater privacy in SFR 21,22,26 and this was consistent with the perceptions of parents that SFR afforded better privacy for bonding and breastfeeding 25 and overall privacy. 26,27 A recent study 20 found that infants in an SFR NICU had significantly longer total days of receiving mothers' breast milk when compared to infants in a standard open-bay unit NICU. However, no studies were located that examined the potential effect of the enhanced privacy on mothers' perceptions concerning milk expression in an SFR NICU.…”
mentioning
confidence: 98%
“…A previous study 2 as well as a large body of anecdotal information has demonstrated that families are more satisfied in private rooms, but are challenged by the isolation this setting imposes upon them. Caregivers, too, recognize that an SFR design improves the sensory environment for newborns and is more desirable for families, but creates communication and collaboration impediments for both families and staff that are not found in open, multi-bed rooms.…”
Section: Gustave Le Bonmentioning
confidence: 99%
“…Although there are few studies comparing these 2 models of care, most have reported beneficial effects of the SFR NICU. These include a shorter interval until full enteric feedings; fewer apneic events; reductions in mortality, nosocomial sepsis, 2 length of stay, [3][4][5] rehospitalization, 4 cost, 6 and noise; increases in breastfeeding, 2 family-centered care, parent visitation, privacy and satisfaction 3,[6][7][8] ; more positive staff perceptions of the environment 2 and job quality 9 and less nurse anxiety. 10 However, negative effects have also been reported including increased number of staff, 10 poorer quality of staff interaction, 9,11 and increased maternal stress.…”
mentioning
confidence: 99%